Adsorption of the aurocyanide, Au (CN)2 - complex on granular activated carbons derived from macadamia nut shells: A preliminary study - Poinern, G.; Senanayake, G.; Shah, N.; Thi-Le, X.; Parkinson, Gordon; Fawcett, D. (2011)
In this study, waste macadamia nut shells were investigated for potential use as a hard organic precursor for the production of a granular activated carbon material. The processing of the macadamia shells commenced with the carbonised of the shells under a nitrogen atmosphere. This was followed by the physical activation of the shells under a carbon dioxide atmosphere, which was carried out at different temperatures to investigate the effect of the activation temperature on pore formation. The pore structure and gold loading capacity of the synthesised activated carbons were investigated. The porous nature and surface structure of the macadamia shell based activated carbon were examined by Scanning Electron Microscopy (SEM) at various stages of manufacture. In addition, gold loading studies were carried out in conjunction with elemental mapping of the activated carbon surface to determine the gold adsorption sites. The studies have revealed that the macadamia shell based carbons, activated at higher temperatures have a gold loading capacity that is comparable to the commercially available coconut based activated carbons. © 2011 Elsevier Ltd. All rights reserved.